1999
DOI: 10.1002/(sici)1521-3927(19990101)20:1<26::aid-marc26>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous free-radical polymerization of styrene in supercritical CO2

Abstract: SUMMARY: The free-radical polymerization of styrene has been studied in the homogeneous phase of supercritical (sc) CO 2 at 80 8C and pressures between 200 and 1 500 bar. 2,29-Azobisisobutyronitrile is used as initiator and CBr 4 as chain-transfer agent. The polymerization is monitored by means of online FT-IR/NIR spectroscopy. In the presence of CO 2 a solution polymerization may be carried out up to a considerable degree of monomer conversion. At 500 bar, for example, maximum styrene conversions of 34.4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 10 publications
3
49
0
1
Order By: Relevance
“…[24][25][26] In particular, the significant reduction in viscosity of the reaction mixture is attractive for studying diffusion-controlled reactions, such as radical-radical termination reactions. [25,27,28] The viscosity of monomeric styrene, for instance, at 80 8C and 300 bar is reduced by 36% when using approximately 20 wt.-% of CO 2 as solvent, [29] and the melt viscosity of common polymers is lowered to a much larger extent, that is by about two orders of magnitude. [30] We recently demonstrated the applicability of CO 2 as a solvent for RAFT polymerization and achieved excellent molecular weight control when using CDB (see Scheme 3) as the mediating agent for styrene polymerization in CO 2 .…”
Section: Introductionsupporting
confidence: 89%
“…[24][25][26] In particular, the significant reduction in viscosity of the reaction mixture is attractive for studying diffusion-controlled reactions, such as radical-radical termination reactions. [25,27,28] The viscosity of monomeric styrene, for instance, at 80 8C and 300 bar is reduced by 36% when using approximately 20 wt.-% of CO 2 as solvent, [29] and the melt viscosity of common polymers is lowered to a much larger extent, that is by about two orders of magnitude. [30] We recently demonstrated the applicability of CO 2 as a solvent for RAFT polymerization and achieved excellent molecular weight control when using CDB (see Scheme 3) as the mediating agent for styrene polymerization in CO 2 .…”
Section: Introductionsupporting
confidence: 89%
“…Royer et al [19], e.g., reported a decrease in viscosity of polymer systems of close to one order of magnitude when 20 wt.-% of fluid CO 2 were added. For styrene polymerizations carried out in the presence of fluid CO 2 an increase of the termination rate coefficient by around one order of magnitude was observed [20], impressively demonstrating the influence of system mobility on the diffusion-controlled termination reaction. In contrast, the rate coefficient of the chemically controlled propagation reaction, k p , remains unchanged [21].…”
Section: Introductionsupporting
confidence: 63%
“…(It should be noted that the inhibition effect observed in CDB-mediated RAFT systems was not determined systematically for this study, because the highpressure experimental set-up does not easily allow for a sufficiently accurate polymerization rate measurement in the early polymerization stage.) Ad (i): The decrease in the overall polymerization rate, when going from a conventional solvent (toluene in this study) or bulk to a fluid carbon dioxide system, was reported earlier for styrene polymerizations and has been attributed to an enhanced termination rate in CO 2 systems [20] because k p was found to remain unchanged when fluid CO 2 was used as the solvent. Fig.…”
Section: Rate Of Polymerizationmentioning
confidence: 99%
“…91 This has been attributed to the poor polymer solubility in scCO 2 , leading to a more compact coil, which in turn results in a higher termination rate. 90,92,93 At intermediate/high conversion, translational diffusion of polymer chains is the rate-determining step, and the low viscosity of scCO 2 would then be expected to cause an increase in k t relative to the corresponding bulk/solution system. The initiation process can also be affected by scCO 2 -it has been reported that 2,2 0 -azobis(isobutyronitrile) (AIBN) decomposes more slowly in scCO 2 than in benzene (at the same temperature and pressure), but that the initiator efficiency is a factor of 1.5 higher in scCO 2 .…”
Section: As Polymerization Mediummentioning
confidence: 80%
“…However, the propagation rate in scCO 2 for MMA, 85 butyl acrylate, 85 as well as other acrylates/methacrylates 86 (but not S 87,88 ) is reduced by $40% (i.e., compared to what would be expected based on dilution only), which has been proposed to be caused by a reduction in the local monomer concentration in the vicinity of the radical chain end (PLP yields the product of k p and local monomer concentration). 83,84,86 At low conversion (in the conversion regime where segmental diffusion is rate determining for termination 89 ), the value of k t is much higher in scCO 2 than in bulk for S 90 and butyl acrylate. 91 This has been attributed to the poor polymer solubility in scCO 2 , leading to a more compact coil, which in turn results in a higher termination rate.…”
Section: As Polymerization Mediummentioning
confidence: 99%